2010
DOI: 10.1161/circgenetics.109.917039
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of the Insulin-Induced Gene 2 Identifies a Variant Associated With LDL Cholesterol and Total Apolipoprotein B Levels

Abstract: Background-In a whole-genome scan, a single nucleotide polymorphism (SNP) (rs7566605) upstream of the insulin-induced gene 2 (INSIG2) was shown to influence body mass index and obesity in the Framingham Heart Study, with replication of these results in an additional 4 of 5 studies. However, other studies could not replicate the association. Because INSIG2 plays an important role in cholesterol biosynthesis, we hypothesized that human INSIG2 variants might play a role in the regulation of plasma lipid and lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Our study also found a protective effect on LDL (those with the minor allele, G, of SNP rs12464355 had lower levels). This finding replicates a previous report of an association between rs12464355 and LDL[ 35 ]). Our failure to identify association between SNP rs7566605 and lipid levels is consistent with previous studies [ 12 , 13 , 14 , 24 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study also found a protective effect on LDL (those with the minor allele, G, of SNP rs12464355 had lower levels). This finding replicates a previous report of an association between rs12464355 and LDL[ 35 ]). Our failure to identify association between SNP rs7566605 and lipid levels is consistent with previous studies [ 12 , 13 , 14 , 24 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there are single nucleotide polymorphisms (SNPs) within the human SETDB2 locus that are associated with metabolic disease traits including glycosylated hemoglobin (HGVPM569), systolic blood pressure (HGVPM563), fasting plasma insulin (HGVPM822), and serum cholesterol (HGVPM568). Additionally, SNPs near the human INSIG2 locus have been associated with obesity and lipid metabolism (Do et al, 2010; Herbert, 2006; Hotta et al, 2008; Kaulfers et al, 2015). Also, SETDB2 is induced by Dex in other metabolic tissues such as white adipose and skeletal muscle (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the INSIG2 polymorphism rs9308762 has been associated with adiposity measures in the Samoan population and in a population of 1,495 Hispanics (11). Although most studies have focused on the association of INSIG2 variants with adiposity measures, others have also explored associations with related metabolic traits such as plasma lipids and glucose homeostasis (11, 17, 19, 21, 26, 2830). Results from these studies are not consistent either.…”
Section: Discussionmentioning
confidence: 99%